A converging artery-sized model for shear adhesion mapping of particles. (15th April 2021) - Asaad, Yathreb; Epshtein, Mark; Korin, Netanel
Abstract: Drug carriers for targeting cardiovascular diseases have been gaining a respectable attention, however, designing such carriers is challenging due to the biophysical complexity of the vascular system. Wall shear stress (WSS), exerted by blood flow on the endothelium surface, is a crucial factor in the circulatory system. WSS affects the adhesion and preferential accumulation of drug carriers. Here, we propose, an innovative approach to investigate particle adhesion in a converging artery-sized model, lined with human endothelial cells. Unlike widely used microfluidic and in vivo setups, our model enables to investigate particle accumulation in a continuous WSS range, performed in a single experiment, and at the right scale relevant for human arteries. First, we characterized the flow and the WSS map along the designed model, which can span along the entire arterial WSS range. We then used the model to examine the effect of particle size and the suspension buffer on particle adhesion distribution. The results demonstrated the role of particle size, where the same particles with a diameter of 2 µm exhibit shear-decreased adhesion while 500 nm particles exhibit shear-enhanced adhesion. Furthermore, under the same WSS, particles show a similar behavior when suspended in a Dextran buffer, having a viscosity analogous to blood, compared to a phosphate buffer solution without Dextran. Moreover, experiments with RBCs in the phosphate buffer, at a 40% physiological hematocrit, decreased particle adhesion and affected their deposition pattern. Altogether, our study suggests an original platform for investigating and optimizing intravascular drug carriers and their targeting properties.